The genesis of the notions “values”, “social values” and the development of social values of future preschool teachers - Kapustina, O. (Problems of Engineer-Pedagogical Education, 2020)
The article focuses on the need to reconsider the concept of «values» in the context of reforming the education system of modern Ukraine. The current state of education development and the state of the research into the question of values are considered through the prism of ongoing changes and transformations that are currently taking place in our country. The paper highlights the importance of aiding future preschool teachers in developing social values. The contemporary scientific community focuses on the fact that the issue of values has been sufficiently researched, but at the same time it requires a more detailed study with regard to future preschool teachers, taking into account the specifics and peculiarities of training specialists in this field of education. In addition, the existing views on the aforementioned issue are analyzed in detail, and the importance of developing social values in the present conditions is revealed. The article deals with different approaches to defining the notion of «values» in Ukrainian scientific literature. The most relevant definitions of this concept are clarified in the paper. Values are found to act as certain ideals, views that are important to society. At the same time, value is an individual’s construct which can act as the main factor in one’s behavior and social activity. We also present significant, in our opinion, categories of values, such as spiritual, absolute, fundamental, moral and others. Such important concepts as «social values», «development of social values» and «development of future preschool teachers’ social values» are substantiated. Based on the analysis of scientific sources, taking into account the current educational requirements, we propose our own definition of such concepts as «social values», «development of future preschool teachers’ social values». In general, the article reveals the modern requirements for future teachers in the conditions of the development of Ukraine as a European state, considers the question of developing values as the most important issue in training future pedagogues, substantiates that it is highly important for future preschool teachers to develop social values and suggests a new definition of this concept.